Asiaticoside reverses M2 phenotype macrophage polarization-evoked osteosarcoma cell malignant behaviour by TRAF6/NF-κB inhibition - Dang-ke Li; Guang-hui Wang (Pharmaceutical Biology, 2022)
Context M2 phenotype macrophage polarization is an attractive target for therapeutic intervention. Asiaticoside (ATS) has multiple pharmacological functions.Objective This study investigates the effect of ATS on M2 phenotype macrophage polarization in osteosarcoma.Materials and methods The differentiation of human THP-1 monocytes into M0 phenotype macrophages was induced by 100 nM phorbol myristate acetate for 24 h, and treated with 20 ng/mL IL-4 and 20 ng/mL IL-13 for 48 h to obtain M2 phenotype macrophages. The function of ATS on the growth and invasion was investigated by cell counting kit-8, transwell, and western blot under the co-culture of M2 phenotype macrophages and osteosarcoma cells for 24 h. The mechanism of ATS on osteosarcoma was assessed using molecular experiments.Results ATS reduced the THP-1 cell viability with an IC50 of 128.67 μM. Also, ATS repressed the M2 phenotype macrophage polarization induced by IL-4/IL-13, and the effect was most notably at a 40 μM dose. ATS (40 μM) restrained the growth and invasion of osteosarcoma cells induced by M2 phenotype macrophages. In addition, ATS reduced the tumour necrosis factor receptor-associated factor 6 (TRAF6)/NF-κB activity in osteosarcoma cells and the TRAF6 knockdown reduced the growth and invasion of osteosarcoma cells induced by M2 phenotype macrophages. TRAF6 (2 μg/mL) attenuated the inhibitory effect of ATS on the growth and invasion of osteosarcoma cells caused by M2 phenotype macrophages. In vivo studies further confirmed ATS (2.5, 5, or 10 mg/kg) repressed osteosarcoma tumour growth.Discussion and conclusions ATS reversed M2 phenotype macrophage polarization-evoked osteosarcoma cell malignant behaviour by reducing TRAF6/NF-κB activity, suggesting ATS might be a promising drug for the clinical treatment of osteosarcoma.